Evaluation, Supervision and Environmental Control - Carbajal Ponce de Rivera, María Paola (2014)
The purpose of this article is to introduce the competencies of OEFA, the way this organization has been implementing mechanisms for its exercise and the liabilities of the administered regarding supervision and control.